Frailty in Nonalcoholic Fatty Liver Cirrhosis: A Comparison with Alcoholic Cirrhosis, Risk Patterns, and Impact on Prognosis - Lubomir Skladany; Pavol Molcan; Jana Vnencakova; Petra Vrbova; Michal Kukla; Lukas Laffers; Tomas Koller (Canadian Journal of Gastroenterology and Hepatology, 2021)
Background. Physical frailty increases susceptibility to stressors and predicts adverse outcomes of cirrhosis. Data on disease course in different etiologies are scarce, so we aimed to compare the prevalence and risk factors of frailty and its impact on prognosis in nonalcoholic fatty liver (NAFLD) and alcoholic (ALD) cirrhosis. Patients and Methods. Cirrhosis registry RH7 operates since 2014 and includes hospitalized patients with decompensated cirrhosis, pre-LT evaluation, or curable hepatocellular carcinoma (HCC). From the RH7, we identified 280 ALD and 105 NAFLD patients with at least 6 months of follow-up. Results. Patients with NAFLD compared with ALD were older and had a higher proportion of females, higher body mass index (BMI) and mid-arm circumference (MAC), lower MELD score, CRP, and lower proportion of refractory ascites. The liver frailty index did not differ, and the prevalence of HCC was higher (17.1 vs. 6.8%, p=0.002). Age, sex, serum albumin, and C-reactive protein (CRP) were independent predictors of frailty. In NAFLD, frailty was also associated with BMI and MAC and in ALD, with the MELD score. The Cox model adjusted for age, sex, MELD, CRP, HCC, and LFI showed that NAFLD patients had higher all-cause mortality (HR = 1.88 95% CI 1.32–2.67, p<0.001) and were more sensitive to the increase in LFI (HR = 1.51, 95% CI 1.05–2.2). Conclusion. Patients with NAFLD cirrhosis had a comparable prevalence of frailty compared to ALD. Although prognostic indices showed less advanced disease, NAFLD patients were more sensitive to frailty, which reflected their higher overall disease burden and led to higher all-cause mortality.